Quality of life workers of polyvinyl chloride production - O. A. Diakovich; M. И. Diakovich (Acta Biomedica Scientifica, 2013)
1,2-dichloroethane comes in the air of the working area. Workers exposed to this production of low concentrations of toxic substances that may lead to the development of various pathologies. It is important not only for the assessment of health data of professional examinations, but also for a subjective self-assessment of the workers. Investigation of health-related quality of life is widespread among patients with various pathologies and among the working population. The aim was to evaluate the quality of life in persons exposed to vinyl chloride and 1,2-dichloroethane. The objects of the study were 154 polyvinyl chloride workers (main group), 84 males, who comparable with those of the main group by sex, age and social conditions, not in contact in his work with the harmful physical and chemical factors (comparison group). Quality of life studied by a questionnaire MOS SF-36. An automated system of quantitative risk assessment of the major pathology syndromes (ASKORS) is used for prenosological diagnostics. Mathematical and statistical analyzes were conducted using Statistica 8. The fewer number of people with the highest level of risk were in the main group, which can be linked to strict pre-employment medical screening and annual professional examinations in the chemical industry. Investigation of quality of life have shown excess of all its components in the main group in relation to the comparison group. The lowest ratings of quality of life, obtained on the scale of role physical and emotional functioning in both groups suggests that the restriction of daily activities related to health problems and emotional instability has production stipulation. The structure of the risks of the major syndromes were similar in the studied groups, and can be considered a response to the impact of production and psychosocial factors. In general, polyvinyl chloride workers assess their quality of life is much higher than the control group.